Synthesis, cytotoxic activities and molecular modeling studies of_x000D_ some 2-aminonaphtho[2,3-d][1,3]thiazole-4,9-dione derivatives - (:unkn) unknown (My University, 2020)
Quinones, especially 1,4-naphthoquinones, are one of the most significant and widely distributedphytochemical groups in nature. 1,4-Naphthoquinones and their synthetic derivatives are found to possessremarkable cytotoxic activities. In this study, a series of 2-aminonaphtho[2,3-d][1,3]thiazole-4,9-dionederivatives were synthesized and their structures were verified with spectral analysis. In vitro cytotoxic activitiesof the synthesized compounds were evaluated by using MTT assay against MKN-45 (Human Gastric cancer),MDA-MB-231 (Human Breast cancer) and HeLa (Human Cervical cancer) cell lines. Among the synthesizedcompounds, 3d inhibited MDA-MB-cell proliferation with an IC50 value of 0.276 µM. Compound 3a inhibitedHeLa and MKN-45 cell proliferation with IC50 values of 0.336 µM and 8.769 µM, respectively. Compound 3binhibited HELA cell proliferation with an IC50 value of 0.269 µM. Molecular docking results suggest that theligands may bind to the hDNA TopoIIβ binding pocket and partially exert their effects. These results proposethat 2-aminonaphtho[2,3-d]thiazole-4,9-dion core has important biological effects and further explorations areworthwhile.